Analisis PT. Indofood CBP Sukses Makmur TBK Produsen Mie Instan Terbesar di Dunia - Patricia; Stella; Billy (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The most dominant instant noodle brand in Nigeria is Indomie. Indomie is a joint venture with Indofood. Various types of instant noodles have been successfully exported to foreign countries. One of the instant noodle company's expansion targets is a country at the westernmost tip of the African continent, Senegal. The objective achieved through this research is to determine the impact of product development of Indofood Brand Instant Noodles on the image of the Indomie brand in the world. PT. Indofood Sukses Makmur Tbk carried out this export activity for the first time, namely in 1992. The product that was first exported out was Indomie products. Indomie products were exported abroad for the first time, with the main reason being that many Indonesian citizens (WNI) live abroad. Countries that are the main marketing destinations for export activities are actually countries with many Indonesian citizens, such as Hong Kong, Saudi Arabia, Taiwan, Malaysia and Singapore. But over time, Indomie is increasingly known and there are more and more enthusiasts. Therefore, its export destinations are expanding to almost the whole world. Keyword: Indomie, Export, Overseas, Instant Noodles, Companies